Deforming mandibular osteomyelitis in a cow caused by Trueperella pyogenes - Caffaro, Karen Antas (2014)
This study reports an unusual case of deforming mandibular osteomyelitis in a cow caused by Trueperella (Arcanobacterium) pyogenes, on the face of the ventrolateral caudal portion of the right branch of the mandible. Fragment aspired of lesion by fine needle allowed cytological characterization, isolation and identification of T. pyogenes. Radiographic examination showed marked periosteal reaction in the right mandible, numerous lytic areas and cortical bone destruction. Despite of treatment based on in vitro antimicrobial sensitivity test, it was recommended the euthanasia due to progressive worsening of the cow's condition. Multiple abscesses were observed in the mandibular region at necropsy. Pyogranuloma was characterized in histological exam. Sampled material collected from the lesion after necropsy resulted in microbiological reisolation of T. pyogenes